Linking management practices and soil properties to Ecosystem Services in Mediterranean mixed orchards - Ioannidou, Sotiroula; Litskas, Vassilis D.; Stavrinides, Menelaos; Vogiatzakis, Ioannis N. (My University, 2022)
Orchards in insular, mountainous environments provide a range of Ecosystem Services (ES). However, research on the benefits of mixed orchards to ES remains very limited. We use Cyprus as a model to study the ES provided by 52 mixed orchards in Organic (Org) and Conventional (Con) farms. The orchards comprised different tree species including pome and stone fruits, nuts and other crops. A framework was developed to link soil quality parameters, orchard attributes and Agricultural Management Practices (AMPs) to the provision of ES. Cluster analysis based on AMPs, orchard attributes and soil properties separated the orchards into a Con and an Org cluster. There were significant differences in soil quality parameters between Org and Con orchards: aggregate stability (Mean Weight Diameter; MWD mm) (Org: 12.5; Con: 9.3), organic matter content (OM %) (Org: 1.15; Con: 0.92), seed bank (number of species) (Org: 6.6; Con: 3.4), Arbuscular Mycorrhizal Fungi (AMF; % of roots colonization) (Org: 31.3; Con: 19.3) and soil respiration (mg CO2/100 g soil dry weight/day) (Org: 36.3; Con: 21.7). Soil types did not differ between the two systems. Using the parameters AMF presence, aggregate stability and organic matter content as proxies for soil biology, physics and chemistry, respectively, we show that Org orchards have a higher potential to provide ES than Con. The results of the study are useful for selecting agricultural management practices to maintain and optimize ES in Mediterranean island mixed orchards.
Keywords: Agricultural practices; CICES; Organic farming; Soil quality; Conventional farming; Cyprus